Constituting Public Support for the National Stem Cell Project: Kungmin as a Rhetorical Flag in South Korean Media. (December 2015) - Chekar, Choon Key
Abstract: The global stem cell scandal widely known as the 'Hwang scandal' was a reminder of the somewhat taken‐for‐granted fact that the South Korean public is often referenced and addressed as kungmin in media discourse. Kungmin, which means 'South Korean nationals', has considerable purchase in everyday life in South Korea as a constant reminder of nationhood. Using Michael Billig's concept of banal nationalism as the key theoretical linchpin of analysis, this article argues that kungmin was a readily available, powerful rhetorical tool for the uncritically pro‐science and profit‐driven South Korean media to justify its support for Hwang's stem cell breakthroughs in the name of kungmin . The general public's support for Hwang was framed as a 'natural' response even after the revelation of unethical procurement of human oocysts and scientific fraud. The article also considers how this politicized representation of the South Korean public restricted the opportunities for democratic social debate on this controversial biotechnology.